Evaluation of Assessment Projects in English Language Education: A Bibliometric Review - Oya, Abas (Bumi Publikasi Nusantara, 2024)
This bibliometric review provides a comprehensive evaluation of assessment projects in English language education from 2013 to 2023. Utilizing data indexed by Google Scholar and analyzed through Publish or Perish, VOSviewer, and Microsoft Excel, the study encompassed 1000 articles to assess publication trends, research focuses, and methodological advancements within the field. The peak in publication activity in 2021 highlights a period of intensive scholarly interest, followed by a notable decline, suggesting a potential shift in research trajectories or saturation in certain topics. Key research areas, such as the efficacy of assessments, the integration of digital tools, and self-assessment methods, emerged as central themes. These focal points were vividly depicted through network and density visualizations, revealing a landscape marked by periods of concentrated activity and a diversity of researched topics. The study's findings underscore the responsiveness of the academic community to evolving educational practices and technological innovations. The culmination of the bibliometric analysis and text mining techniques provided nuanced insights into the evolution of English language assessment, spotlighting the necessity for continuous development in the field to address emerging challenges in educational assessment practices.